El Comité Mudaliar (1962): evaluación de los comienzos - Carballido Coria, Laura (El Colegio de México, 2020)
The Mudaliar Committee was set up in the early years of postcolonial India to assess the population’s health and to make recommendations. It sought to generate knowledge to grant legitimacy to the State and inform public health policy-making. Mudaliar professed that he was highly critical, yet the report produced by him and the Committee’s other members had several limitations and contradictions. In analyzing this process, the author seeks to improve our understanding of the early postcolonial period, and to show that the shift from colonial rule to independence cannot be simplified as a clean break or as seamless, straightforward continuities.